2017
DOI: 10.1039/c7cp01328k
|View full text |Cite
|
Sign up to set email alerts
|

Does H4SO5 exist?

Abstract: The possible existence of HSO in aqueous sulfuric acid is analyzed in detail. For bare HSO, the computed free energy barrier for the exergonic transformation of HSO into the HSOHO complex is only 3.8 kcal mol. The presence of water or sulfuric acid catalyzes the dehydration to such an extent that it becomes almost a barrierless process. In the gas phase, dehydration of HSO is an autocatalytic reaction as the water molecule produced by the decomposition of one HSO molecule induces further dissociation. Thus, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The reaction H2O + SO4 2-(+2H + ) ↔ HSO5 3-+ H + (+2H + ) proceeds to the right with an equilibrium constant K(25°) = 9.1×10 36 , thus G o = 211 kJ/mol (50 kcal/mol) [4]. However, HSO5 3is not stable in nonacidic solution [4,5], and this was stated very clearly (in Ref. 5, on p. 11683): "…HSO5 3is stable only under strongly acidic conditions, and it collapses to the tetrahedral SO4 2structure upon neutralization."…”
mentioning
confidence: 99%
“…The reaction H2O + SO4 2-(+2H + ) ↔ HSO5 3-+ H + (+2H + ) proceeds to the right with an equilibrium constant K(25°) = 9.1×10 36 , thus G o = 211 kJ/mol (50 kcal/mol) [4]. However, HSO5 3is not stable in nonacidic solution [4,5], and this was stated very clearly (in Ref. 5, on p. 11683): "…HSO5 3is stable only under strongly acidic conditions, and it collapses to the tetrahedral SO4 2structure upon neutralization."…”
mentioning
confidence: 99%
“…These constraints have been sufficient to successfully explore the PESs of several molecular clusters. [22,28,[30][31][32] Once it was determined how the initial structures would be constructed, a hierarchical screening was established so that the initial structures were optimized at the PBE0/D95V level and then refined at the PBE0-D3/def2-TZVP level. [33][34][35] Each structure was characterized as a true minimum by harmonic vibrational frequency analysis.…”
Section: Computational Detailsmentioning
confidence: 99%
“…This conclusion was supported by the absence of one O═S═O vibrational band at 1,150 cm −1 , which is a characteristic of H 2 SO 4 . Murillo et al [44] explored the possible existence of H 4 SO 5 and found that the computed free energy barrier for the transformation of H 4 SO 5 into the H 2 SO 4 ─H 2 O complex is only 3.8 kcal mol −1 . These authors further proposed that in the gas phase, dehydration of H 4 SO 5 is an autocatalytic reaction as the water molecule produced by the decomposition of one H 4 SO 5 molecule induces further dissociation.…”
Section: Sulfuric Acidmentioning
confidence: 99%